Binding of thymopoietin to the acetylcholine receptor. - Venkatasubramanian, K (1986)
Thymopoietin is a polypeptide hormone of the thymus with physiological effects on the immune system and on acetylcholine-mediated transmission at the neuromuscular synapse. Elucidation of the structure and function of the nicotinic acetylcholine receptor has been facilitated by the use of the electric organs of Torpedo ray or Electrophorus eel as rich sources of the receptor and by the use of snake polypeptide toxins such as alpha-bungarotoxin as highly selective labels of the acetylcholine binding site. We now show that thymopoietin binds with high affinity (Ka approximately equal to 2.5 X 10(9) M-1) to the acetylcholine binding region of the acetylcholine receptor of Torpedo californica, as evidenced by similar and complete inhibition of the binding of radiolabeled thymopoietin or alpha-bungarotoxin by either of these polypeptides. These findings raise intriguing questions concerning the mechanisms whereby alpha-bungarotoxin and the thymopoietin affect acetylcholine receptor function, since these two polypeptides with such similar binding properties have very different functional effects.